2016
DOI: 10.3389/fnagi.2016.00025
|View full text |Cite
|
Sign up to set email alerts
|

Increased Hippocampus–Medial Prefrontal Cortex Resting-State Functional Connectivity and Memory Function after Tai Chi Chuan Practice in Elder Adults

Abstract: Previous studies provide evidence that aging is associated with the decline of memory function and alterations in the hippocampal (HPC) function, including functional connectivity to the medial prefrontal cortex (mPFC). In this study, we investigated if longitudinal (12-week) Tai Chi Chuan and Baduanjin practice can improve memory function and modulate HPC resting-state functional connectivity (rs-FC). Memory function measurements and resting-state functional magnetic resonance imaging (rs-fMRI) were applied a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
130
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(141 citation statements)
references
References 76 publications
9
130
0
2
Order By: Relevance
“…Investigators have also found decreased functional connectivity between the right hippocampus and superior mPFC in SCD (Hu et al, 2016). In a previous study, we found that mind-body intervention can significantly modulate hippocampus-mPFC rsFC and that this change is associated with memory function changes (Tao et al, 2016). Thus, our results align with previous findings.…”
Section: Discussionsupporting
confidence: 92%
“…Investigators have also found decreased functional connectivity between the right hippocampus and superior mPFC in SCD (Hu et al, 2016). In a previous study, we found that mind-body intervention can significantly modulate hippocampus-mPFC rsFC and that this change is associated with memory function changes (Tao et al, 2016). Thus, our results align with previous findings.…”
Section: Discussionsupporting
confidence: 92%
“…Niemannand colleagues found that increases in motor fitness and regular exercise increased hippocampal volume in older adults [75]. As a further support of our findings, we found that Tai Chi Chuan exercise significantly enhanced the resting state functional connectivity between the hippocampus and medial prefrontal cortex (mPFC) [76]. Li and colleagues also found that a multimodal intervention including cognitive training, Tai Chi Chuan exercise, and group counseling improved the resting-state connectivity between the mPFC and MTL[77].…”
Section: Discussionsupporting
confidence: 85%
“…It is designed to assess global memory function as measured by memory quotient (MQ), as well as memory function subscores (mental control, picture recognition, visual reproduction, associative learning, touch, comprehension memory, digit span) [63]. In this study, we focused on the subscores of the WMS-CR since the modulation effect of Tai Chi Chuan and Baduanjin on the MQ has been published in a previous study [64]. …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a recent clinical study demonstrated that extensive practice of Tai Chi, an activity that includes attention to upright posture, improved memory performance more than walking (Mortimer et al, 2012). Another study found that Baduanjin Qigong, a less strenuous movement form that also involves attention to posture, improved memory as much as Tai Chi (Tao et al, 2016). Together, these studies suggest that it is not (only) the cardiovascular aspect of exercise that leads to memory improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Little research has been done on the cognitive correlates of stooped posture. However, a recent study found that practice of Qigong, a form of mindful movement that includes a focus on upright posture, led to improvement on a test of memory (Tao et al, 2016). Therefore, an association between upright posture and memory is plausible.…”
Section: Introductionmentioning
confidence: 99%